Best practices on informed consent procedures in sensitive areas of medical practice - Schwarzová, Aneta (Bioethica, 2025)
The contribution focuses on best practices regarding informed consent procedures in sensitive areas of medical practice, specifically death with dignity. Initially, attention is given to defining key terms such as active euthanasia, assisted suicide, dignity, and psychological suffering. Subsequently, the paper analyzes the current situation in selected states, examining legislation, draft laws, jurisprudence, etc. Finally, a comparison of the legislation of individual states is provided.